2016
DOI: 10.1007/s00167-016-4191-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of graft bending angle during knee motion after outside-in, trans-portal and trans-tibial anterior cruciate ligament reconstruction

Abstract: Therapeutic study (prospective comparative study), Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 62 publications
(130 reference statements)
0
42
0
Order By: Relevance
“…Secondly, the range of motion examined in the dynamic activity was limited and knee flexion over 90° was not examined. Previous studies on GBA during knee motion have shown lower bending angle of reconstructed grafts in over 90° knee flexion than in 0° to 30° flexion 32,64 , therefore assessment of motion at these lower flexion angles should be clinically relevant. Thirdly, we didn’t have a trans-tibial control group, which might have lower GBA at 0° knee flexion 33,64 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Secondly, the range of motion examined in the dynamic activity was limited and knee flexion over 90° was not examined. Previous studies on GBA during knee motion have shown lower bending angle of reconstructed grafts in over 90° knee flexion than in 0° to 30° flexion 32,64 , therefore assessment of motion at these lower flexion angles should be clinically relevant. Thirdly, we didn’t have a trans-tibial control group, which might have lower GBA at 0° knee flexion 33,64 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies on GBA during knee motion have shown lower bending angle of reconstructed grafts in over 90° knee flexion than in 0° to 30° flexion 32,64 , therefore assessment of motion at these lower flexion angles should be clinically relevant. Thirdly, we didn’t have a trans-tibial control group, which might have lower GBA at 0° knee flexion 33,64 . However, in clinical practice, we didn’t use the trans-tibial technique during this period because it could sometimes lead to non-anatomical tunnel positions 8-12 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the clinical relevance of this finding has yet to be determined, in theory an acute GBA will cause higher stress at the proximal bone-graft interface and negatively affect graft healing and remodeling. 33…”
Section: Discussionmentioning
confidence: 99%
“…T he article "In vivo analysis of graft bending angle in anterior cruciate ligament reconstructed knees during downward running and level walking: Comparison of flexible and rigid drills for trans-portal technique" 1 by Tashiro, Sundaram, Thorhauer, Gale, Anderst, Irrgang, Fu, and Tashman attempts to add to the understanding of this concept and shed light on the potential clinical impact. Many other publications [2][3][4][5][6][7][8][9] have evaluated graft bending angle (GBA) and the effect that drilling technique has. These reviews include the effects of variations within anatomic anterior cruciate ligament drilling such as type of drill, where we are drilling from, and where the drill exits.…”
mentioning
confidence: 99%